A Novel Ideal Floating Inductor Using Translinear Conveyors - Iqbal A. Khan; Mehmood H. Zaidi (Active and Passive Electronic Components)
An ideal floating inductor circuit using translinear conveyors is introduced. The floating inductor simulator uses two translinear conveyors and a single capacitor in its realization. The circuit provides the current controlled ideal floating inductance without any component matching constraints. Simulation results on the floating inductor simulator verify the theory